LEGAL REVIEW OF ARTICLE 156 PARAGRAPH 2 OF LAW NO. 13 OF 2003 CONCERNING EMPLOYMENT WITH GOVERNMENT SUPERVISION OF THE FULFILLMENT OF SEVERANCE PAY RIGHTS FOR WORKERS EXPERIENCING TERMINATION OF EMPLOYMENT - Susilowati, Asih (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Justice for workers and employers is the goal of development in the field of labor in Indonesia. Such justice is highly dependent on the quality of labor law that regulates the employment relationship between workers and employers. If labor laws and other regulations are of poor quality, they will lead to disputes that eventually lead to termination of employment. Based on the fact that the injustice that occurs in termination of employment is caused by problematic legal system factors, the legal culture of the community, and the existence of mutual conflicts between Company Regulations, Collective Labor Agreements, and Work Agreements with applicable laws and regulations . The research method used is normative juridical, research that discusses doctrines or principles in legal science. Using primary legal materials, namely binding legal materials. While the primary legal material of this research is Law Number 13 of 2003 concerning Manpower, Secondary Legal Materials consist of books and legal doctrines. The results show that labor law as represented in Labor Law Number 13 of 2003 concerning Manpower, is felt to be imperfect so that it cannot provide solutions to injustice in the process of terminating employment. Therefore, the provisions in labor law as referred to in Labor Law Number 13 of 2003 concerning Manpower need to be continuously improved, especially the provisions in the Articles that cause injustice to workers and employers related to Termination of Employment.